Effect Of A Lactobacilli Probiotic On Longevity And Mobility Of Male Drosophila Melanogaster With Alzheimer’s Disease - Chin Peng, Lim (Pusat Pengajian Teknologi Industri, 2020)
Approximately 50 million people are diagnosed with Alzheimer’s disease (AD) in the world as reported in 2019. Locomotor impairment were present in the early stage of the disease and the decline in the performance of AD patients is often related to aging. Effective treatment has yet to be conducted extensively even though considerable amounts of studies had been performed.